Endogenous separations, wage rigidities and unemployment volatility - Mikael Carlsson; Andreas Westermark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
We show that in microdata, as well as in a search and matching model with flexible wages for new hires, wage rigidities of incumbent workers have substantial effects on separations and unemployment volatility. Allowing for an empirically relevant degree of wage rigidities for incumbent workers drives unemployment volatility, as well as the volatility of vacancies and tightness to that in the data. Thus, the degree of wage rigidity for newly hired workers is not a sufficient statistic for determining the effect of wage rigidities on macroeconomic outcomes. This finding affects the interpretation of a large empirical literature on wage rigidities.
Keywords: E30; J63; J64; 330; Search and matching; Unemployment volatility puzzle; Wage rigidities; Job Destruction